Agronomic Performance of Cowpea Cultivars During the Second Cropping Season in Southwest Minas Gerais, Brazil - Antônio Augusto Nogueira Franco; Ricardo Shigueru Okumura; Letícia Priscilla Arantes; Franciane Diniz Cogo; Samy Pimenta; Daiane de Cinque Mariano; Abner José de Carvalho; Ana Carolina Petri Gonçalves; Marcos Vinicius Bohrer Monteiro Siqueira (Agriculture, 2025)
The cowpea (Vigna unguiculata (L.) Walp.) is well adapted to high temperatures, water deficits and low fertility soils, being widely cultivated in regions less favorable to common beans. Its grains are rich in proteins, vitamins and minerals, representing an important food source and a promising alternative for producing protein at low cost, in a short space of time, given the precocity of its cycle. However, in the state of Minas Gerais there is only a recommendation for one cowpea cultivar, the Poços de Caldas cultivar. In addition to being quite old, it is no longer found in crop production fields. Our objective was to provide local farmers with new cultivar options that exhibit high yield potential, appropriate plant architecture for mechanized cultivation, and superior grain health and quality. The experiments were conducted in Passos city, Brazil, during the second cropping season of the 2021, 2022, and 2023 years. Ten commercial cowpea cultivars were assessed in a randomized block design with five replications, considering morphophysiological traits and phytotechnical yield components. Treatment effects were analyzed using the Scott-Knott test, a statistical method that compares treatments and identifies significant differences among them. The thousand-seed weight and grain index showed a positive correlation with grain yield. The least productive cultivars had the longest pods and, consequently, the highest number of grains per pod. The 2022 and 2023 years provided the most favorable morphophysiological conditions for cowpea cultivation, which significantly enhanced productivity. Among the tested cultivars, BRS Xique-Xique, BRS Novaera, BRS Tumucumaque, and BRS Pajeú were the most suitable for a second cropping season cultivation in the Southwest region of Minas Gerais, while BRS Marataoã, BRS Itaim, and BRS Rouxinol were the least. We emphasize the need for further studies to support the establishment and expansion of cowpea cultivation in this region.